Analysis of the Use of Artificial Intelligence (AI) in Literacy Learning in Elementary Schools Challenges and Opportunities for Teachers: Systematic Literature Review - Tria Uli Wardani; Darwanto (Universitas Pendidikan Ganesha, 2026)
The utilization of Artificial Intelligence (AI) in literacy learning at the elementary school level has become an important concern alongside the rapid development of digital transformation in education. AI integration is considered capable of creating learning environments that are more adaptive, interactive, and student-centered; however, its implementation still faces various pedagogical and technical challenges. This study aims to analyze the utilization of AI in elementary school literacy learning and to explore the challenges and opportunities of its implementation for teachers. This study employed a Systematic Literature Review method by examining relevant scientific articles related to the use of AI in literacy learning. The research subjects consisted of scientific articles discussing the implementation of AI in the context of elementary education. Data were collected through documentation studies using article analysis sheets and literature selection guidelines as instruments. The data were analyzed using descriptive qualitative analysis through the stages of identification, selection, evaluation, and literature synthesis. The findings show that AI supports students’ literacy development and teachers’ competence through more personalized learning. However, its implementation remains limited by infrastructure, teacher readiness, and ethical and data security issues. The implications of this study emphasize the importance of teacher training and the pedagogical integration of AI to create effective, inclusive, and sustainable literacy learning.